Music in German Silent Cinema : Reception in the Film Trade Press 1907-1925 - Beinroth, Carolin and Bullerjahn, Claudia (Journal of Film Music, 2019)
Whereas sounds in American early cinema have been examined by Rick Altman for his ground-breaking book Silent Film Sounds, published in 2004, the musical components of German early cinema remain largely unexamined. Previous research on silent film sound in Germany primarily relied on the contemporary music press and neglected the film press, even though the latter offers much evidence on the topic. Thus, for the first author's master's thesis two of Germany's most important film trade presses were examined: Der Kinematograph and Die LichtBildBühne with the supplement Das Kino-Orchester. As a result, previously unknown facts about the use of music in German silent cinema were discovered, which will be described in this article. The aim of this article is to shed light on German silent film sound practices and to compare them to those prevailing in the USA.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTU1OC9qZm0uMzA5NzE